2015
DOI: 10.1002/adom.201500209
|View full text |Cite
|
Sign up to set email alerts
|

Adaptable Ultraviolet Reflecting Polymeric Multilayer Coatings of High Refractive Index Contrast

Abstract: a series of undesirable photoreactions promoted by the absorption of UV photons, which lead to the deterioration of their mechanical and optical properties. Polymers are usually transparent to part of the UV spectrum, so a commonly employed synthetic strategy to attain UV blocking fi lms is based on embedding inorganic [3][4][5][6][7] or organic [8][9][10] UV absorbers within a polymeric matrix. The main drawback of this approximation is the short term durability of the shielding effect as a result of the phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…In addition, nanoparticles are not preferred especially for cosmetic applications because growing evidence suggests that the nanoparticles could be hazardous to human health. Furthermore, a multilayer film, Bragg reflector, can be fabricated by repeated vapor deposition of ZrO 2 and SiO 2 , which can also efficiently reflect UV,4,7 but it has angle‐dependency. By contrast, colloidal glasses or correlated amorphous colloidal structures8–19 may show strong angle‐independent UV reflection when “intraparticle” or “interparticle” backscattering resonance conditions4,7 are matched for UV.…”
Section: Figurementioning
confidence: 99%
“…In addition, nanoparticles are not preferred especially for cosmetic applications because growing evidence suggests that the nanoparticles could be hazardous to human health. Furthermore, a multilayer film, Bragg reflector, can be fabricated by repeated vapor deposition of ZrO 2 and SiO 2 , which can also efficiently reflect UV,4,7 but it has angle‐dependency. By contrast, colloidal glasses or correlated amorphous colloidal structures8–19 may show strong angle‐independent UV reflection when “intraparticle” or “interparticle” backscattering resonance conditions4,7 are matched for UV.…”
Section: Figurementioning
confidence: 99%
“…Although a high RI contrast and good optical device quality were achieved, the sensitivity toward vapors is severely reduced due to the limited textural porosity of the titania layer. Another approach to increase the RI contrast is to identify new porous materials with a similar or even higher RI compared to TiO 2 , although current alternatives such as WO 3 sol ( n = 2.03), ZrO 2 nanoparticles ( n = 1.70), Ta 2 O 5 nanoparticles ( n = 1.80), undoped or antimony‐doped SnO 2 films ( n (undoped) = 1.83, n (3% Sb‐doped) = 2.34) all feature lower RIs compared to dense titania or suffer from low transparency in the visible range. Thus, the highest RI contrast BSs reported so far combine highly porous silica layers stacked with dense titania layers, exhibiting an RI contrast of Δ n = 0.83, Δ n = 0.84, and Δ n = 0.89 .…”
Section: Introductionmentioning
confidence: 99%
“…and nanoscale. Micro-and nanostructures have been reported to modify the optical properties of the polymer surface by providing antireflective properties [20,21] or reflective ones, which allows the use as photonic crystals [22], to modify the hydrophobic or hydrophilic character [21,23], or to improve light harvesting for more efficient organic solar cells [24]. In particular, surface structuring of carbon-based polymer composites by nanoimprint lithography (NIL) has been reported to modify the wettability and mechanical properties of the materials [25] and demonstrated that the fabrication of materials with different functionalities is possible by combining the use of fillers and the control of the surface structure.…”
Section: Introductionmentioning
confidence: 99%